FILSAFAT MANUSIA ALI SYARI’ATI: KESADARAN DAN KEBEBASAN MANUSIA DI ERA REVOLUSI TEKNOLOGI 4.0 - Fitri Cahyanto (Academic Journal of Islamic Principles and Philosophy, 2020)
Human philosophy began to be studied rationally since ancient Greece. Now human philosophy is still a field of study that continues to be developed in accordance with the spirit of his era. Ali Syari’ati was a Muslim figure who succeeded in producing human philosophy, by using an empirical ratio approach and not letting go of Islamic dogma. This study attempts to uncover and represent Syari’ati’s philosophical human thought using an historical continuity approach, critical analysis, and description of interpretation. The era of technological advances, everything is fast-paced, especially in the combination of infotek and biotech that is packaged in one big data and the emergence of artificial intelligence that is able to work like humans is even better. In essence, technology is a tool found by humans to become an extension, not to become an authority holder of human will. Technology now takes on the vital task of man, namely human awareness and freedom, a core part of the indicator that humans are fully human. Through human philosophy Ali Syari’ati tried to restore human nature to stay aware and free of himself in making a decision